The Role of Linguistics on Influencing Community Associations on Social Media: A Socio-Semantic Study of Commodity Advertisements - Masud Muhammadiah; Muta’allim; Nawiruddin; Lela Susanty; Zarkasi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2025)
In the digital era, commodity advertisements on social media use persuasive language to create associations within user communities. This research examines the role of linguistics on influencing community associations on social media through commodity advertisements, using a socio-semiotic study approach. By employing socio-semiotic linguistic theory, the study analyzes how word choices, symbols, and connotations used in advertisements can shape social perceptions and community identities. This research was qualitative in nature. The data in this study consists of words, phrases, and symbols, while the data sources were commodity advertisements on social media. The method used to collect the data is content analysis. The researcher listens to the words, symbols, and the connotative meanings embedded in the advertisements. The data was analyzed using a socio-semiotic approach, focusing on the linguistic and symbolic elements within the advertisements. The study finds that carefully crafted language in commodity advertisements significantly influences consumer perceptions, strengthens social bonds, and shapes collective identities. Moreover, the findings from this research suggest that the choice of words or phrases in advertisements for each commodity must create a positive impression in the public's consciousness. Thus, beyond simply informing, the language used should also touch the emotional aspect of the audience, prompting them to purchase the product to fulfill their needs. This study contributes to the understanding of how language influences consumer behavior and provides practical implications for marketers in creating more persuasive advertisements